Global trends in research on irritable bowel syndrome and the brain-gut axis: Bibliometrics and visualization analysis - Peng-Ning Wu; Shuai Xiong; Peng Zhong; Wan-Qing Yang; Min Chen; Tai-Chun Tang (Frontiers Media S.A., 2022)
Irritable bowel syndrome (IBS) is a gastrointestinal disorder with no structural damage, and its pathogenesis remains unclear. Studies have shown that the brain-gut axis is closely related to the occurrence of IBS. However, studies of IBS related to the brain-gut axis have not been systematically analyzed by bibliometrics and visual analysis. This study is based on 631 publications in the Web of Science Core Collection (WoSCC) to analyze hot spots and trends in this field. The collaborations between different authors, institutions, countries, and keywords were bibliometrically analyzed by CiteSpace software. Meanwhile, VOSviewer analyzed the references. The results show that since 2012, the number of publications has been growing rapidly. According to the collaborative network analysis, the United States, the National University of Ireland, Cork, and J.F. Cryan are the countries, institutions, and authors contributing the most, respectively. Through keywords and literature analysis, mechanisms and therapy associated with IBS and the brain-gut axis have still been a research focus in recent years. Furthermore, the physiological and pathological mechanisms of the brain-gut axis influencing IBS (related to gastrointestinal dysfunction, vagus nerve, visceral pain, intestinal flora, serotonin, tryptophan metabolism, stress, brain-derived neurotrophic factor (BDNF), and malonyldialdehyde) are the future research trends, especially the mechanisms related to intestinal flora. This is the first bibliometric and visualization analysis of IBS and brain-gut axis-related literature to explore research hotspots and trends.